MLN-4760 Induces Oxidative Stress without Blood Pressure and Behavioural Alterations in SHRs: Roles of Nfe2l2 Gene, Nitric Oxide and Hydrogen Sulfide - Michal Kluknavsky; Andrea Micurova; Martina Cebova; Ezgi Şaman; Sona Cacanyiova; Iveta Bernatova (Antioxidants, 2022)
Reduced angiotensin 1–7 bioavailability due to inhibition of angiotensin-converting enzyme 2 (ACE2) may contribute to increased mortality in hypertensive individuals during COVID-19. However, effects of ACE2 inhibitor MLN-4760 in brain functions remain unknown. We investigated the selected behavioural and hemodynamic parameters in spontaneously hypertensive rats (SHRs) after a 2-week s.c. infusion of MLN-4760 (dose 1 mg/kg/day). The biochemical and molecular effects of MLN-4760 were investigated in the brainstem and blood plasma. MLN-4760 had no effects on hemodynamic and behavioural parameters. However, MLN-4760 increased plasma hydrogen sulfide (H2S) level and total nitric oxide (NO) synthase activity and conjugated dienes in the brainstem. Increased NO synthase activity correlated positively with gene expression of Nos3 while plasma H2S levels correlated positively with gene expressions of H2S-producing enzymes Mpst, Cth and Cbs. MLN-4760 administration increased gene expression of Ace2, Sod1, Sod2, Gpx4 and Hmox1, which positively correlated with expression of Nfe2l2 gene encoding the redox-sensitive transcription factor NRF2. Collectively, MLN-4760 did not exacerbate pre-existing hypertension and behavioural hyperactivity/anxiety in SHRs. However, MLN-4760-induced oxidative damage in brainstem was associated with activation of NO- and H2S-mediated compensatory mechanisms and with increased gene expression of antioxidant, NO- and H2S-producing enzymes that all correlated positively with elevated Nfe2l2 expression.